Outbreak of equine pythiosis in a southeastern region of Brazil: Environmental isolation and phylogeny - Paz, Giselle Souza da [UNESP]; Camargo, Gabriel Gasparini [UNESP]; Cury, José Eduardo; Apolonio, Emanuel Vitor Pereira [UNESP]; Garces, Hans Garcia [UNESP]; Prado, Ana Carolina do [UNESP]; Chechi, Jessica Luana [UNESP]; Oliveira, Alana Lucena [UNESP]; Watanabe, Marcos Jun [UNESP]; Bagagli, Eduardo [UNESP]; Bosco, Sandra de Moraes Gimenes [UNESP] (Hindawi, 2021)
Pythiosis is a disease caused by the oomycete Pythium insidiosum, mainly reported in equines, dogs and humans and directly transmitted through contaminant zoospores in aquatic environments. We report the first outbreak of equine pythiosis in five equines. Wound samples were submitted for diagnostic testing including mycological culture and nested PCR. Treatment approaches consisted of conventional and alternative therapies. Microbiological analyses were performed using water samples from the riverbanks close to where the animals had grazed. All animals were positive for P. insidiosum cultures, and two animals responded successfully to alternative therapy (ozone therapy). After culture and molecular analysis of environmental samples, the presence of P. insidiosum in one section of the Tietê River was confirmed through a 99% sequence identity. Phylogenetic analyses using the cytochrome oxidase II gene showed that the animal isolates clustered in clade I and the environmental isolates clustered in clade III. Although the environmental and wound isolates belonged to different genetic clades, we concluded that the Tietê River is an important source of infection by P. insidiosum and that research concerning environmental isolation of P. insidiosum from rivers and lakes should be strongly facilitated in Brazil.
Keywords: ecological niche; horse; oomycetes; ozone therapy; Pythium insidiosum